1970
DOI: 10.14214/ma.6728
|View full text |Cite
|
Sign up to set email alerts
|

Männyn ja kuusen kasvun vaihtelu Suomessa 1964–1993

Abstract: Valtakunnan metsien viimeisimmät inventointitulokset osoittavat männyn ja kuusen kasvun alentuneen Suomen eteläosassa selvästi 1990-luvun alussa. Käsitystä kuusten vaikeuksista tukevat eri puolilla Etelä-Suomea löytyvät kuolleet yksilöt. Samantyyppinen ilmiö havaittiin 1930-luvun puolivälissä, jolloin Esko Kangas aloitti tutkimuksensa kuusen kuivumistyypeistä. Tämänkertaisen kuusen kuivumisen syyt ovat herättäneet vilkasta keskustelua sekä tutkija-että maallikkopiireissä. Kuivuus, routa, talviaikainen hengitys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Observations by Henttonen (1990) and Mielikäinen et al (1996) showing that growth variation of Norway spruce in Finland is also related to precipitation are based on data from more southern regions than those sampled for this study. The effect of precipitation on tree growth is known to increase on moving southwards from the northernmost regions in Sweden (Jonsson 1969).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Observations by Henttonen (1990) and Mielikäinen et al (1996) showing that growth variation of Norway spruce in Finland is also related to precipitation are based on data from more southern regions than those sampled for this study. The effect of precipitation on tree growth is known to increase on moving southwards from the northernmost regions in Sweden (Jonsson 1969).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, growth variation of conifers in central Europe is most strongly correlated with precipitation (e.g., Eckstein et al 1989;Kahle 1994). In recent studies, the effect of precipitation on annual growth of Norway spruce has also been demonstrated in southern and central Finland (Henttonen 1990;Mielikäinen et al 1996). Furthermore, on soils with low waterholding capacity, a significant correlation between July precipitation and annual ring width of Scots pine (Pinus sylvestris L.) has been reported in central Norway (Slåstad 1957) and near the Arctic timberline in Finland (Kärenlampi 1972).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Henttonen 1984;Miina 2000;Salminen and Jalkanen 2004;Salminen et al 2009). The effect of precipitation is usually considered to be of minor importance for Scots pine growing under Finnish conditions, as the evaporative demand is low in relation to precipitation (Mielikäinen et al 1996;Miina 2000). Contradictorily, Henttonen (1984) suggested that precipitation sum during May to July of the previous summer affected tree ring growth in Scots pine.…”
Section: Introductionmentioning
confidence: 99%